eCALIBRATOR: A Comparative Tool to Identify Key Genes and Pathways for Eucalyptus Defense Against Biotic Stressors - du Toit, Yves; Coles, Donovin William; Mewalal, Ritesh; Christie, Nanette; Naidoo, Sanushka (Frontiers in Microbiology, 2020)
Many pests and pathogens threaten Eucalyptus plantations. The study of defense responses in this economically important wood and fiber crop enables the discovery of novel pathways and genes, which may be adopted to improve resistance. Various functional genomics experiments have been conducted in Eucalyptus-biotic stress interactions following the availability of the Eucalyptus grandis genome, however, comparisons between these studies were limited largely due to a lack of comparative tools. To this end, we developed eCALIBRATOR http://ecalibrator.bi.up.ac.za, a tool for the comparison of Eucalyptus biotic stress interaction. The tool, which is not limited to Eucalyptus, allows the comparison of various datasets, provides a visual output in the form of Venn diagrams and clustering and extraction of lists for gene ontology enrichment analyses. We also demonstrate the usefulness of the tool in revealing pathways and key gene targets to further functionally characterize. We identified 708 differentially expressed E. grandis genes in common among responses to the insect pest Leptocybe invasa, oomycete pathogen Phytophthora cinnamomi and fungus Chrysoporthe austroafricana. Within this set of genes, one of the Gene Ontology terms enriched was “response to organonitrogen compound,” with NITRATE TRANSPORTER 2.5 (NRT2.5) being a key gene, up-regulated under susceptible interactions and down-regulated under resistant interactions. Although previous functional genetics studies in Arabidopsis thaliana support a role in nitrate acquisition and remobilization under long-term nitrate starvation, the importance of NRT2.5 in plant defense is unclear. The T-DNA mutants of AtNRT2.5 were more resistant to Pseudomonas syringae pv. tomato pv tomato DC3000 inoculation than the wild-type counterpart, supporting a direct role for NRT2.5 in plant defense. Future studies will focus on characterizing the Eucalyptus ortholog of NRT2.5.